FUNCTIONAL ACTIVITY AMONG WORKERS IN HOME INDUSTRY OF MELINJO CHIPS AT PLUMBON VILLAGE - Marta Cintia Dewi; Nur Setiawati Dewi (Jurnal Keperawatan Diponegoro, 2012)
Functional activities is a potential ability performed by an individual to perform normal activities and duties as expected. Evaluation of the functional activity of  workers is important to be done to improve the labor productivity. The purpose of this study was to determine the functional activity of the workers. The research was conducted using cross sectional approach with 166 samples. The research was conducted in February-March 2012 in melinjo home industry at Plumbon village. Functional activity was assessed by using the instrument of Back Pain Function Scale (BPFS) which has been translated into Indonesian language. Research results showed an average score of functional activity in  melinjo chips workers was 54.46.  Suggestion from this study for community nurses especially occupational nurse is making efforts to increase the functional activity score of melinjo chips workers